2012
DOI: 10.3724/sp.j.1263.2011.00215
|View full text |Cite
|
Sign up to set email alerts
|

Reduced peripheral vascular reactivity in refractory angina pectoris: Effect of enhanced external counterpulsation

Abstract: AimsTo examine if the skin microvascular bed is altered and can be modified by enhanced external counterpulsation (EECP) in patients with chronic refractory angina.MethodsTwenty patients diagnosed with refractory angina were divided into EECP (n = 10) or no EECP (n = 10) groups. The data were compared to matched healthy subjects (n = 20). The cutaneous forearm microvascular blood flow was measured by Laser-Doppler flowmetry. The vascular responsiveness to iontophoretic administration of acetylcholine (ACh), so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Recently, Bondesson et al (2011) reported that EECP did not elicit improvement in superficial subcutaneous vessels of the forearm in patients with CAD when assessed using a laser-Doppler probe. However, numerous phenotypic differences exist between the subcutaneous and skeletal muscle resistance arteries.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Bondesson et al (2011) reported that EECP did not elicit improvement in superficial subcutaneous vessels of the forearm in patients with CAD when assessed using a laser-Doppler probe. However, numerous phenotypic differences exist between the subcutaneous and skeletal muscle resistance arteries.…”
Section: Discussionmentioning
confidence: 98%